Clinical variation in the organization of clinical pathways in esophagogastric cancer, a mixed method multiple case study - J. C. H. B. M. Luijten; P. A. J. Vissers; L. Brom; M. de Bièvre; J. Buijsen; T. Rozema; N. Haj Mohammad; P. van Duijvendijk; E. A. Kouwenhoven; W. J. Eshuis; C. Rosman; P. D. Siersema; et al. (BMC, 2022)
Abstract Background Among esophagogastric cancer patients, the probability of having undergone treatment with curative intent has been shown to vary, depending on the hospital of diagnosis. However, little is known about the factors that contribute to this variation. In this study, we sought to understand the organization of clinical pathways and their association with variation in practice. Methods A mixed-method study using quantitative and qualitative data was conducted. Quantitative data were obtained from the Netherlands Cancer Registry (e.g., outpatient clinic consultations and diagnostic procedures). For qualitative data, thematic content analysis was performed using semi-structured interviews (n = 30), observations of outpatient clinic consultations (n = 26), and multidisciplinary team meetings (MDTM, n = 16) in eight hospitals, to assess clinicians' perspectives regarding the clinical pathways. Results Quantitative analyses showed that patients more often underwent surgical consultation prior to the MDTM in hospitals associated with a high probability of receiving treatment with curative intent, but more often consulted with a geriatrician in hospitals associated with a low probability of such treatment. The organization of clinical pathways was analyzed quantitatively at three levels: regional, local, and patient levels. At a regional level, hospitals differed in terms of the number of patients discussed during the MDTM. At the local level, the revision of radiological images and restaging after neoadjuvant treatment varied. At the patient level, some hospitals routinely conduct fitness tests, whereas others estimated the patient's physical fitness during an outpatient clinic consultation. Few clinicians performed a standard geriatric consultation in older patients to assess their mental fitness and frailty. Conclusion Surgical consultation prior to MDTM was more often conducted in hospitals associated with a high probability of receiving treatment with curative intent, whereas a geriatrician was consulted more often in hospitals associated with a low probability of receiving such treatment.